Clinical Utility of Bronchoalveolar Lavage in Pediatric Oncology Patients. Issue 11 (20th July 2022) - Shanthikumar, Shivanthan; Colenutt, Samuel; Cole, Theresa; Conyers, Rachel; Rozen, Tom; Harrison, Jo; Robinson, Philip; Haeusler, Gabrielle M.
Abstract : Background: Lower airway sampling is important in the assessment of lower respiratory tract infection in children with cancer or posthematopoietic stem cell transplant and can be done via bronchoalveolar lavage (BAL). Clinicians can struggle with balancing the benefits of BAL against the risks. This study aimed to define the diagnostic and clinical utility of BAL in this population. Methods: A single-center retrospective review of BAL performed in children with cancer or posthematopoietic stem cell transplant. Data extracted included demographics, BAL method and results and antimicrobial treatment. Variables significantly associated with diagnostic yield, diagnostic impact (confirmation or exclusion of infection), and clinical impact (any change in antimicrobial or nonantimicrobial therapy) were assessed in both univariate and multivariate analysis. Results: Seventy-three BAL episodes were included. In 26 (35.6%) episodes, a pathogen was identified on BAL. Forty-nine (67%) BAL episodes had a diagnostic impact and 15 (21%) had a clinical impact. Late BAL (>72 hours) compared with early BAL (odds ratio 3.27; 95% CI: 1.03–10.86), and flexible bronchoscopy compared with nonbronchoscopic lavage (odds ratio 6.10; 95% CI: 1.90–24.0), were more likely to have a diagnostic impact on multivariate analysis. No associations were found for clinical impact. Conclusions: One-third of BAL episodes identified a pathogen, two-thirds had a diagnostic impact, and almost a quarter of episodes impacted antimicrobial prescribing. The method and timing of BAL may be important, with flexible bronchoscopy 6-fold more likely and late BAL 3-fold more likely to have a diagnostic impact.